A project‐level analysis of value creation in firms. Issue 2 (14th April 2019) - Cohn, Jonathan B.; Gurun, Umit G.; Moussawi, Rabih
Abstract: This paper analyzes value creation in firms at the project level. We present evidence that managers facing short‐termist incentives set a lower threshold for accepting projects. Using novel data on new client and product announcements in both the U.S. and international markets, we find that the market responds less positively to a new project announcement when the firm's managers have incentives to focus on short‐term stock price performance. Furthermore, textual analysis of project announcements shows that firms with short‐termist chief executive officers use vaguer and generically positive language when introducing new projects to the marketplace.